The Use of Lip Bumper in Lip Sucking Treatment - Yulie Emilda Akwan; Ayulistya Paramita; Eriza Juniar (Denta Journal Kedokteran Gigi, 2017)
Background: Oral habits include habit which are continuously done and has the potential to cause defects on teeth and perioral tissues.Lip sucking or biting habits are often found simultaneously or as a substitution of finger sucking. This habit may affect the labial and perioral structures. The habit may take several forms. Two extreme types are mild wetting of the lips with the tongue and pulling the lips into the mouth between the teeth. The lip bumper is a functional device that is used successfully to intercept developing dental and occlusal problems by allowing a proper development of the arch length and width for eruption of the permanent teeth.Purpose: This study aimed to re-validate the effectiveness of lip bumper application and habitual therapy in treating the bad habit of lip sucking. Case Report: The mother of a 9-year-old girl reported an upper front teeth protrusion and frequent occurrence of mouth ulcer. Further examination revealed that the patient had a habit of lip sucking. Case Management: Removable Lip Bumper is used to control lip habits such as lip sucking and to improve mentalis muscle hyperactivity. Such habit was treated with the use of a removable lip bumper and habitual therapy conducted by both parents. Constants reminder and encouragement from the parent to wear the lip bumper is one of the key success factors in this treatment. Conclusion: Five months after the initial application of a lip bumper and habitual therapy, the patient overcame the habit of lip sucking.